IS SLEEP DURATION CORRELATE TO THE ANTHROPOMETRIC MEASUREMENTS AND INSULIN LEVELS IN OBESE ADOLESCENTS? INVESTIGATION WITH A CROSS-SECTIONAL STUDY - Eva Ardianah; Nur Aisiyah Widjaja; Tausyiah Rohmah Noviyanti; Yoppi Yeremia Alexander; Yasmine Nurfirdaus; Rino Tryanto Keya; Edi Hermanto; Iitdrie; Welldelin Yufuria Christiansi (Universitas Airlangga, 2026)
Introduction: Insufficient sleep has been shown to increase the risk of obesity by 6%. Aim: To investigate the effect of sleep duration on anthropometric measurements and insulin levels among obese adolescents. Methods: A cross-sectional study was conducted in September–October 2019 among obese students in Surabaya and Sidoarjo. Sleep duration, anthropometric measurements, and insulin levels were assessed. Statistical analyses included tests of normality, independent samples t-tests or Mann–Whitney U tests, and Pearson’s correlation analysis. Results: A total of 165 obese adolescents were recruited. Participants with shorter sleep duration were older than those with recommended sleep duration. Male adolescents predominated over females (111 vs. 54). Sleep duration was associated with body mass index (BMI); adolescents with recommended sleep duration had a lower BMI compared to those with shorter sleep duration (33.86 ± 5.17 vs. 35.61 ± 5.12 kg/m², p = 0.049) and a smaller hip circumference (109.71 ± 9.98 vs. 113.49 ± 10.74 cm, p = 0.038). Other anthropometric parameters (waist circumference, body weight, and height) did not differ significantly between groups. Insulin levels were also lower in adolescents with recommended sleep duration compared to those with shorter sleep duration (23.35 ± 12.95 vs. 30.84 ± 16.92 μU/mL, p = 0.001). Weak correlations were observed between sleep duration and BMI, BMI-for-age z-score, hip circumference, and insulin levels. Conclusion: Sleep duration is correlated with BMI, hip circumference, and insulin levels among obese adolescents.